Effect of different insecticides against Aphis gossypi population in chili crop / Amirul Amin Haizir - Haizir, Amirul Amin (Faculty of Plantation and Agrotechnology, 2018)
A study was conducted at sharefarm of Universiti Teknologi MARA (UiTM) Malacca, Jasin campus to illustrate the relationship between different insecticides against aphid population in chilli crops. The treatments of the research were T1: Malathion (57%) @ 2.2mL/litre, T2: Cypermethrin (20%) @ 0.5mL/liter , T3: Neem organic bio-pesticide at 450g/litre and T4: control treatment. Efficacy of 3 types of insecticides, Malathion (57%), Cypermethrin (20%) and neem organic bio-pesticide have been evaluated on chili plants in reducing pest population on namely Aphis gossypi. The chili plants were arranged in the Randomized Complete Block Design (RCBD) with 6 blocks. Result showed that Malathion (57%) was the most effective against aphid population followed by neem organic bio-pesticide. While Cypermethrin (20%) was found to be the most least effective in reducing Aphis gossypii population. The study was found that there were significant relationship between insecticides and other parameters such as number of flowers, marketable fruits and unmarketable fruits. The result also once again showed that Malathion(57%) is the most positive effect-giving insecticide followed by Neem bioinsecticide and Cypermethrin (20%).